Validity and reliability of the Modified Tardieu Scale as a spasticity outcome measure of the upper limbs in adults with neurological conditions: a systematic review and narrative analysis. Issue 12 (24th December 2021) - Shu, Xiaoyi; McConaghy, Ciara; Knight, Alec
Abstract : Purpose: To evaluate published evidence on the Modified Tardieu Scale (MTS) as a tool to assess spasticity in the upper limbs of adults with neurological conditions. Data sources: A systematic search of six electronic databases (PubMed/MEDLINE, CINAHL, EMBASE, the Cochrane Library, Web of Science and Physiotherapy Evidence Database) from inception to 31 December 2020. A search strategy was developed using key elements of the research question: population, intervention (action), outcome. Study eligibility criteria: Inclusion criteria: (1) adult participants with neurological conditions; (2) upper limb muscles/joints as tested elements; (3) studies testing the MTS and (4) reliability or validity reported. Exclusion criteria: (1) non-English articles; (2) non-empirical articles and (3) studies testing the Tardieu Scale. Study appraisal: Evidence quality was evaluated using the US National Heart, Lung, Blood Institute quality assessment tool for observational cohort and cross-sectional studies. Results: Six reliability studies met the inclusion criteria. Overall, most articles reported good-to-excellent levels of inter-rater, intrarater and test–retest reliability. However, limitations, such as study design weaknesses, statistical misuses and reporting biases, undermine confidence in reported conclusions. The validity of the MTS also remained questionable based on the results of one study. Conclusions and implications: This review did not find sufficient evidence to either support or reject the use of the MTS in assessing spasticity in the upper limbs of adults with neurological conditions. Despite the paucity of research evidence, the MTS may still remain a clinically useful tool to measure the motor aspect of spasticity. Future research would benefit from a focus on test standardisation, while the wider field would require the development of a consensual definition of spasticity.